Experimental-numerical study of wrinkling in rotary-draw bending of Tight Fit Pipes - Naderi, Gholamali; Moussavi Torshizi, Seyed Ebrahim; Dibajian, Seyed Houssain (Thin-walled structures, 2023)
The paper focuses on tight fit pipe (TFP) wrinkling in rotary-draw bending (RDB), where TFP is a double-walled pipe. To this end, a corrosion-resistant alloy liner is fitted inside an outer carbon steel pipe through a thermal-hydraulic manufacturing process. A 3D elastic–plastic finite element (FE) model (the dynamic explicit FEM code ABAQUS/Explicit) is developed in this study. This model simulates the manufacturing process in the first step of the analysis and proceeds in the rotary-draw bending analysis of the lined pipe. Then, in the third step, the springback of the two-layer pipe is analyzed. This integrated three-stage process considers geometric nonlinearities, geometric and thickness imperfections, inelastic material behavior, and contact between the two pipes. Contact pressure during the process in the presence of various imperfections is monitored by the histogram to predict wrinkling. Furthermore, the best bending angle, with minimum possibility of wrinkling in the inner pipe, is obtained by these histograms. ABAQUS scripting via the Python programming language is used to study the effect of various imperfections on RDB. Numerical results on imperfection sensitivity demonstrate the significant influence of imperfections’ amplitude on liner wrinkling. The ovality and thinning of the lined pipe via bending angle were investigated. By comparing the experimental results with those of the simulation, an appropriate agreement is observed. •The bending of Tight Fit Pipe (TFP) is investigated.•In this study, a 3D elastic–plastic FEM model is developed.•This integrated three-stage consider geometric nonlinearities, geometric and thickness imperfections, inelastic.•To prediction of wrinkling, contact pressure during the process in the presence of various imperfections is monitored by the histogram.•Numerical results on imperfection sensitivity demonstrate the significant influence of amplitude of imperfections on liner wrinkling.